AUTOGENIC RELAXATION RESPONSE TO STRESS - ., Kiran; Girgla, Kawalinder K; Chalana, Harsh; Thaman, Richa Ghay (Pakistan Journal of Physiology, 2015)
Background: Psychosocial stress is an important risk factor for psychiatric disorders such as depression and anxiety. Men and women report different reactions to stress, both physically and mentally. Introduction: The aim of this study was to evaluate the difference in gender response to the effect of Rajyoga meditation on chronic tension headache (CTH) and related co morbidities like anxiety and depression. Methods: Fifty-eight patients (35 females and 23 males) patients diagnosed to have CTH according to the International Headache Society Criteria- II were included in this study. Patients were taught Rajyoga meditation, which they practised 20 minutes a day for 8 weeks. Headache intensity was assessed by Visual Analogue Scale (VAS), while Anxiety and Depression were assessed by Hamilton anxiety and depression scale, before and after 8 weeks of meditation. Results: There was a highly significant reduction in anxiety, depression and headache parameters after Rajyoga meditation both in males and females but the percentage relief was more in females as compared to males. Conclusion: The management of CTH, anxiety and depression by tradition methods can become more effective by the adjunct practice of Rajyoga meditation techniques, which have a simple and potential benefit in both genders, more so in females as it potentiates the calmness effect of inner self. Pak J Physiol 2015;11(4):21–3